Study of Psychiatric Disorders in Patients with Psoriasis attending Outpatient Department in a Tertiary Hospital - Joshi, Neelam; Singh, Pradip Man; Shrestha, Shristi (Nepal Medical College Journal, 2021)
The neuro-immuno-cutaneous endocrine model explains the mind-body connection. This model explains how many inflammatory dermatoses are triggered or exacerbated by stress factors. These conditions are called psychophysiological skin diseases. Psoriasis is a common psychophysiological skin disease. It affects 2-4% of the population worldwide and involves multiple systems in the body. The rates of psychiatric comorbidities are high in psoriasis, but still, they are not given due attention which leads to an increase in morbidity and mortality in the long run. This study intends to uncover the psychiatric comorbidities in psoriasis patients. In this study, the prevalence of psychiatric disorders was investigated among 104 patients with psoriasis. Following rating scales were used; Hamilton rating scales for depression and anxiety, Presumptive stressful life event scale, Beck scale for suicidal ideation, and Dermatology life quality index. The prevalence of psychiatric disorders in Psoriasis patients was found to be 66.35%. Among the psychiatric disorders, 29.8 % were dependent on substances, 18.27% were found to be suffering from depression,15.38 % with anxiety disorder and 2.88 % with psychotic disorders. Psoriasis has a high prevalence of psychiatric morbidity.